Assessing the Contribution of E-Governance to Sustainable Educational Development in Nigeria - Miesindou Alagha; Moyosoluwa Dele-Dada (PERSPEKTIF, 2025)
This study rigorously assesses the contribution of e-governance to sustainable educational development in Nigeria, addressing persistent gaps in access, efficiency, and equity. Utilizing a systematic literature review, this paper evaluates key e-governance initiatives (such as JAMB’s digital systems, WAEC’s e-testing, and platforms like uLesson) and assesses their alignment with the Sustainable Development Goals (SDGs), specifically SDG 4 (Quality Education) and SDG 16 (Strong Institutions). Findings confirm that while digital implementation generally enhances transparency, access, and administrative efficiency, its transformative impact is inconsistent due to prevailing systemic challenges, notably infrastructure deficits, disparities in digital literacy, and institutional corruption. The research demonstrates that these underlying issues impede the full realization of e-governance potential. The key contribution of this paper is highlighting the critical need for comprehensive policy reforms, targeted infrastructure investments, and leveraging public-private partnerships to bridge implementation gaps, offering actionable insights for policymakers in emerging economies seeking sustainable digital transformation in education.